INTEGRATING MULTIPLE INTELLIGENCES THEORY IN ENGLISH LANGUAGE TEACHING - Ahmad, Pahrozi - (Premise: Journal of English Education and Applied Linguistics, 2022)
Nine types of multiple intelligence theories are proposed by Gardner (1999), which include the following: verbal-linguistic, musical, logical-mathematical, visual-spatial, bodily-kinesthetic, and existential. Since all these types of intelligence are on an equal footing, educators can use various strategies to help students develop their full potential. Silent Way, Suggestopedia, CLT, etc., are some methods used to incorporate multiple intelligence into teaching and learning activities. However, the use of multiple intelligence in learning English is still rare. This results in teachers not using the most effective methods for teaching and learning the English language. Following the steps outlined in this paper can help teachers integrate at least some of these nine types of intelligence. This paper provides teachers with new ideas for improving the quality of teaching and learning through multiple intelligence. This paper attempts to answer the following questions: 1) What exactly is multiple intelligence, and how can it be encouraged? 2) In the context of teaching English as a foreign language, what methods are most effective in fostering multiple intelligences? This study is descriptive qualitative work being done in preparation for a conceptual paper. The method consists of reviewing all related literature to provide sufficient arguments. The discussion focuses on multiple intelligence theory, English language instruction, and incorporating multiple intelligence into teaching-learning activities.